Online Reviews and Ratings on Mid-segment Mobile Phones: A Perception Study - Raj Vijayanagar, Sundar; Nithin, A.; Rath, Sachidanand; Ranjan, Rahul; Misra, Siddharth (International Journal of Psychosocial Rehabilitation, 2019)
Purpose: This study aims to understand the influence of reviews and ratings on the purchase decision of mid-segment mobile phones based on the demographic profile. Design/Methodology/Answer: Primary data was collected from 200 respondents with the help of a structured questionnaire. Multistage regression using SPSS version 20.0 was adopted to analyze and interpret the results of the collected data. Findings: It was found that demographical characteristics have an influence on purchase decisions based on the reviews and ratings they read on mid-segment mobile phones. Income range has a significant effect on the decision-making. Also, our study has suggested that the age group and gender have no impact on reviews. Practical Implications: This study is important to know how consumers perceive reviews and ratings. Moreover, it is useful for marketers to understand and study the current demand for the product based on the demographic profile, and it will help to elevate the demand to the most desired state. Originality/Value: This paper focuses on filling the gap of demographical influence on purchase decision by reviewing and rating mid-segment mobile phones